27 GX-188E, A therapeutic HPV vaccine, in combination with imiquimod or IL-7-HYFC for treatment of HPV-16 or HPV-18 related cin 3: results from phase 2 study. (18th September 2019) - Park, JS; Lee, SJ; Hur, SY; Kim, TJ; Hong, SR; Lee, JK; Cho, CH; Suh, YS; Woo, JW; Sung, YC
Abstract : Objectives: We conducted a prospective, randomized, phase 2 clinical trial of GX-188E, a therapeutic HPV vaccine in combination with Imiquimod (IMQ) or IL-7-hyFc for HPV-16 or -18 related CIN 3. The primary endpoint was to determine the histopathological regression to <CIN1 assessed at week 20 (W20), and at week 36 (W36). In addition, viral clearance, HPV E6/E7 specific T-cell response and Flt-3L concentration were also assessed. Methods: Hypothesis was that combination of GX-188E with IMQ or IL-7-hyFc could result in synergistic improvement of immune-mediated tumor clearance compared to GX-188E alone. Results: In total, 51 patients were randomized, and 1 dropout occurred due to pregnancy. Among 25 patients receiving GX-188E plus IMQ, 16 (64%) and 18 patients (72%) at W20 and W36 demonstrated histopathological regression, respectively. HPV clearance was observed in 13 (52%) and 15 patients (60%) at W20 and W36, respectively. On the other hand, in patients receiving GX-188E plus IL-7-hyFc, 4 (16%) and 11 out of 25 patients (44%) showed histopathological regression at W20 and W36, respectively. The lower efficacy obtained in GX-188E plus IL-7-hyFc may be attributed to insufficient local delivery of IL-7-hyFc via transcytosis across mucosal layer due to its liquid formulation. Considering vaginal fluid may also disturb mucosal delivery pathway, development of appropriate formulation is necessary. Conclusions: To better understand the mechanism of systemic and local HPV-specific T cell responses induced by GX-188E, immunological analysis including intracellular cytokine staining PBMC, analysis of tumor infiltrating CD4/CD8 T cells and levels of CD69, CD103, and foxp3 are needed.